1989
DOI: 10.1161/01.res.64.1.97
|View full text |Cite
|
Sign up to set email alerts
|

Autoantibodies against beta-adrenoceptors in human idiopathic dilated cardiomyopathy.

Abstract: Although it is recognized that the number of cardiac beta-adrenoceptors is reduced in human dilated cardiomyopathy, the mechanisms involved have not been defined. We examined the possible role of altered humoral immunity by comparing the effect of sera from patients with idiopathic dilated cardiomyopathy (n = 20), ischemic or valvular heart disease (n = 28), or controls with no known cardiac disease (n = 18) on the binding of radioligands to cardiac beta-receptors. The ability of sera from cardiomyopathic pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
111
0
6

Year Published

1992
1992
2009
2009

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 310 publications
(119 citation statements)
references
References 24 publications
2
111
0
6
Order By: Relevance
“…In this study, Ab-mediated activation of PKA was identified in a rat heart cell line and was shown to be mediated by both ␤1-and ␤2-AR. These results are consistent with previous reports suggesting that sera from myocarditis and cardiomyopathy patients contain agonistic autoantibodies that bind to ␤-AR (34,37). Adrenergic receptors, especially ␤1 subtype, not only function to generate second messengers to control the heart contractility, but also to regulate other cardiac functions, myocyte growth, and programmed cell death.…”
Section: Discussionsupporting
confidence: 93%
“…In this study, Ab-mediated activation of PKA was identified in a rat heart cell line and was shown to be mediated by both ␤1-and ␤2-AR. These results are consistent with previous reports suggesting that sera from myocarditis and cardiomyopathy patients contain agonistic autoantibodies that bind to ␤-AR (34,37). Adrenergic receptors, especially ␤1 subtype, not only function to generate second messengers to control the heart contractility, but also to regulate other cardiac functions, myocyte growth, and programmed cell death.…”
Section: Discussionsupporting
confidence: 93%
“…Estos autooanticuerpos también se han observado con diferentes frecuencias en pacientes con cardiopatías de origen no chagásico, incluyendo cardiomiopatía idiopática dilatada, cardiomiopatías isquémicas, arritmias y trastornos de la conducción (7,14,15).…”
Section: Discussionunclassified
“…In particular, autoantibodies against cellular cardiac proteins, like G-protein coupled receptors (e.g., b 1 -adrenergic receptors [13,14]) and muscarinergic receptors (M2), have been identified [15]. In addition, antibodies against membrane components and mitochondrial proteins, especially against the ADP/ATP-carrier protein of the inner mitochondrial membrane, have been associated with the disease [16,17].…”
Section: Introductionmentioning
confidence: 99%